3 Prognostic risk stratification tool (CMR and conventional risk factors) in myocardial infarction with non-obstructed coronary arteries (MINOCA). (18th May 2017) - Dastidar, Amardeep Ghosh; Garate, Estefania De; Rodrigues, Jonathan; Baritussio, Anna; Drobni, Zsofiya; Singhal, Priyanka; Biglino, Giovanni; Angelini, Gianni; Dorman, Stephen; Strange, Julian; Baumbach, Andreas; Johnson, Tom; et al.
Abstract : Introduction: Evidence on the prognostic role of Cardiac ?Magnetic Resonance (CMR) and conventional risk factors in myocardial infarction with non-obstructed coronaries (MINOCA) is lacking. Aim: To assess the prognostic impact of CMR and conventional risk factors in MINOCA. Methods: 402 consecutive MINOCA patients undergoing CMR scan were prospectively followed up for primary clinical endpoint of all-cause mortality. 1.5T CMR was performed using a comprehensive protocol. Patients were grouped into 4 categories based on CMR findings: MI (embolic/spontaneous recanalisation), myocarditis, cardiomyopathy and normal CMR. Results: Overall, CMR was able to identify the cause for the troponin rise in 74% (26% MI, 24% myocarditis and 23% cardiomyopathy). In a mean follow up of 2.5years, 4.5% patients died. Cardiomyopathy group had the worst prognosis (mortality – 12%, log rank 15.97 p=0.001). MI and normal both had 3% mortality and myocarditis 1%. In a multivariate model that included clinical and CMR parameters, CMR diagnosis of cardiomyopathy and ST-segment elevation on presentation ECG remained the only 2 significant predictors of mortality. Using a risk score with 1 point each for presentation as STEMI and CMR diagnosis of cardiomyopathy, the mortality risk rates for a score of 0, 1 and 2 were 2%, 7% and 21% respectively (p<0.0001). Conclusion: A CMR diagnosis was identified in 74% of MINOCA. Cardiomyopathy has the highest mortality, followed by MI and myocarditis. The strongest predictors of mortality were a CMR diagnosis of cardiomyopathy and ST-elevation on presentation ECG, thereby allowing a robust stratification of patients.